THE EFFECT OF SOCIAL INTERACTION ON WORK MOTIVATION MEDIATED BY ORGANIZATIONAL CULTURE IN THE REGIONAL POLICE OF NORTH SUMATRA - Muliono Muliono; Muhammad Isa Indrawan (Lafadz Jaya Publisher, 2023)
This study aims to analyze the effect of social interaction on work motivation in mediating with organizational culture in the North Sumatra Regional Police. This research was conducted at the North Sumatra Police Office. The number in this study was 221 employees. Sampling was carried out using the Slovin Formula so that the sample became 142 employees. This research model uses Path analysis, and the measurement tool uses Smart PLS 3.3.3. The results of this study are Organizational Culture has a positive and significant effect on Work Motivation, Social Interaction has a positive and significant effect on Organizational Culture, Social Interaction has a positive and significant effect on Work Motivation, Social Interaction has a positive and significant effect on Work Motivation through Organizational Culture.